Introduction to the Special Issue: Indigenous Self-determination in Health System Reforms - Gabel, Chelsea; Lavoie, Josée (Health Reform Observer – Observatoire des Réformes de Santé, 2024)
Across Canada, First Nations, Inuit and Métis peoples and communities live in rural, remote, Northern and reserve places, as well as urban places, and experience health inequities when compared with non-Indigenous peoples. These inequities are founded by pervasive colonial ideologies, policies, systems, and practices, many of which persist today resulting in multiple disparities in health as well as social, political, and economic areas (Adelson 2005; Allan and Smylie 2015). In Canada, the federal government’s role in the provision of health services is primarily through the limited public health and prevention services offered by the First Nations and Inuit Health Branch (FNIHB), now Indigenous Services Canada (ISC). Services are offered to status (registered) First Nations living on-reserve and to Inuit living in their traditional territories. They provide non-insured health benefits (NIHB) such as prescription drugs, dental, and vision coverage to all status/registered First Nations and Inuit, regardless of where they live; however, non-insured health benefits are not offered to Métis or non-status First Nations. As a result of historical legislative vagueness, and the multiplicity of authorities that has resulted, the First Nations, Inuit and Métis legislation and health policy framework is very complex, which itself results in a great deal of diversity in health service provision across provinces and territories. The framework fails to adequately address the health care needs of the Métis or First Nations and Inuit people who are either not registered or not living on reserve or in their traditional territory (Lavoie and Gervais 2012). [continued in PDF / HTML]